2004
DOI: 10.1023/b:jarg.0000027019.87795.4e
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight Discordance in Spontaneous Versus Induced Twins: Impact on Perinatal Outcome

Abstract: Purpose : To compare the rate of birth weight discordance and perinatal outcome of twin pregnancies after assisted reproduction with that of spontaneous twins. Method : A total of 12,920 deliveries were analyzed retrospectively. Seventy-five twin pregnancies after ART were compared to the 94 spontaneous counterparts. Birth weight discordance was defined as a difference of 20% or more. Results : Discordance rate was elevated (25.3% vs. 17.0%) among ART twins. SGA was increased and NICU admission was more freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
4
9
0
1
Order By: Relevance
“…Regarding delivery, the induced group had higher rates of caesareans, as described in other studies 21,28 . We found that all the results were independent of chorionicity and the induced method chosen.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding delivery, the induced group had higher rates of caesareans, as described in other studies 21,28 . We found that all the results were independent of chorionicity and the induced method chosen.…”
Section: Discussionsupporting
confidence: 80%
“…This seems to be due to an increase in the age of reproduction, the use of OI and the use of IVF 19 . Studies have shown that singleton pregnancies that are the product of IVF are at an increased risk of preterm delivery, low birth weight, induction of labor, cesarean delivery and pregnancy-induced hypertension compared with SC singleton pregnancies 20,21 . However, studies that have compared IVF with SC twin pregnancies have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…We believe, therefore, that the clear distinctions reported in some of the prior studies deserve careful thought and much further research. Most of the prior studies failed to make any clear mention of the IUI categories, whereas some even grouped IUI with SC (3)(4)(5)(6)8). In our opinion, based on these vague, perhaps even confusing categorizations, the poor maternal and fetal outcomes attributed to ART have yet to be proven.…”
mentioning
confidence: 76%
“…Two contemporary studies found no differences in birthweight discordance by fertility treatment type, though both were more narrowly focused on comparing specific treatments and lacked a comparison group of women conceiving without fertility treatments . Older studies comparing birthweight discordance between assisted reproductive technology and twins conceived without fertility treatments found conflicting results . As has been suggested, based on the available evidence, the greater discordance observed in the medication‐only assisted reproduction group may be due to ovarian hyperstimulation resulting in embryos of different gestational ages due to superovulation or changes in the endometrial environment which negatively impact foetal growth .…”
Section: Commentmentioning
confidence: 99%